Provenance signatures and changes of the southwestern sector of the Barents Ice Sheet during the last deglaciation. (7th November 2017) - Kaparulina, Ekaterina; Junttila, Juho; Strand, Kari; Lunkka, Juha P.
Abstract : Southwestern Barents Sea sediments contain important information on Lateglacial and Holocene environmental development of the area, i.e. sediment provenance characteristics related to ice‐flow patterns and ice drifting from different regional sectors. In this study, we present investigations of clay, heavy minerals, and ice‐rafted debris from three sediment cores obtained from the SW Barents Sea. The sediments studied are subglacial/glaciomarine to marine in origin. The core sequences were divided into three lithostratigraphical units. The lowest, Unit 3, consists of laminated glaciomarine sediments related to regional deglaciation. The overlying Unit 2 is a diamicton, dominated by mud and oversized clasts. Unit 2 reflects a more ice‐proximal glaciomarine sedimentary environment or even a subglacial depositional environment; its deposition may indicate a glacial re‐advance or stillstand during an overall retreat. The uppermost Unit 1 consists of Holocene marine sediments and current‐reworked sedimentary material with a relatively high carbonate content. A significant proportion of the sedimentary material could be derived from Svalbard and transported by sea ice or icebergs to the Barents Sea during the late deglacial phase. The Fennoscandian sources and local Mesozoic strata from the bottom of the Barents Sea are the likely provenances of sediments deposited during the deglacial and ice re‐advance phases. Bottom currents and sea‐ice transport were the main mechanisms influencing sedimentation during the Holocene. Our results indicate that the provenance areas can be reliably related to certain ice‐flow sectors and transport mechanisms in the deglaciated Barents Sea.